HUBUNGAN ANTARA STRESS BELAJAR DENGAN PRESTASI BELAJAR SISWA FULL DAY SCHOOL DI SD AL KAUTSAR KOTA SURABAYA - Rezka Malinda A.S; Nur Irmayanti; Aironi Zuroida (PSIKOWIPA (Psikologi Wijaya Putra), 2020)
This study aims to determine whether there was a relationship between learning stress and student achievement in full day school in Surabaya city. Stress of learning in question was the pressure faced by children related to school that has an impact on physical, psychological health and learning performance. So that there was one relationship that was investigated in this study, namely the correlation between learning stress and learning achievement. This research was conducted on elementary school children with a total of 146 research subjects, consisting of 86 boys and 60 girls covering grades 4 & 5 elementary school. The data collection tool was in the form of a learning stress questionnaire consisting of 30 items and a recapitulation of the report card PAS (end of semester assessment) for 1 year. Data analysis was performed using pearson product moment statistical correlation techniques with the help of the SPSS program (statistical product and service solution) 21. From the analysis of research data obtained correlation values between learning stress with learning achievement of 0,163 with p of 0,488. This shows that there was a significant correlation between learning stress and learning achievement. This means that the higher the stress of learning, the lower the learning achievement of full day school students in SD Surabaya city and vice versa the lower the stress of learning, the higher the learning achievement of full day school students in SD Surabaya city.